Evaluation of Dysphagia in Amyotrophic Lateral Sclerosis - Xiao QIU; Yi WU; Xia ZHAO (康复学报)
Amyotrophic lateral sclerosis (ALS) is a rare disease, dysphagia is one of the most critical issues for ALS patients, which leads to severe malnutrition, aspiration pneumonia and abnormal mental status. One of the most severe and invalidating symptoms faced by many patients with ALS, is oropharyngeal dysphagia, a swallowing disorder that disrupts the ability to move food or liquid safely and efficiently from the mouth through the pharynx into the esophagus. Swallowing deficits may also worsen patients'quality of life. Nearly all patients with ALS manifest bulbar involvement in advanced disease. There is almost none study of dysphagia in patients with ALS, we reviewed recent advances of evaluation of dysphagia in ALS patients, including screening of dysphagia, clinical assessment, scale, equipment evaluation and psychological assessment. Research of dysphagia in patients with ALS in China is seldom studied and needs attention.